2008
DOI: 10.1080/03009740802001426
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren's syndrome in men

Abstract: Although pSS is typically a disease affecting women, clinicians should be aware that it may be diagnosed in male patients. Except for haematological presentation, we could not find any notable differences in clinical and immunological characteristics between male and female patients with pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 38 publications
1
42
5
Order By: Relevance
“…Alveolitis displayed a strong tendency in the exploratory cohort which was confirmed after the meta-analysis, though the observation should be interpreted with caution considering the low numbers. A higher frequency of pulmonary involvement in male patients has been suggested by previous studies [34, 37], though statistical significance was not reached in these investigations. Also, lymphadenopathy has been associated with male sex [36, 37, 39].…”
Section: Discussioncontrasting
confidence: 62%
“…Alveolitis displayed a strong tendency in the exploratory cohort which was confirmed after the meta-analysis, though the observation should be interpreted with caution considering the low numbers. A higher frequency of pulmonary involvement in male patients has been suggested by previous studies [34, 37], though statistical significance was not reached in these investigations. Also, lymphadenopathy has been associated with male sex [36, 37, 39].…”
Section: Discussioncontrasting
confidence: 62%
“…Many studies have reported anti-SSA to be lower in men with primary SS, however a majority of studies have not found a consistent difference in serological status between men and women. [7][8][9][10][11][27][28][29][30] Also, we compared the proportion of seropositivity for either anti-SSA, anti-SSB, and/or ANA by gender, which has not been done before. Interestingly, men were four times more likely to be negative for all three tests compared to women.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported men to have a lower prevalence of positive serologic tests (such as anti-SSA and anti-SSB); however, there is no clear consensus regarding the frequency of extraglandular manifestations by gender. [7][8][9][10][11] Despite the higher incidence rate of SS in women, the mortality rate has been noted to be almost three times higher in men compared to women. 12 This disparity in the severity of clinical manifestations may be due to gender differences in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence is higher in females than in males, with a female-to-male ratio of 9:1. Although SS may occur at any age, including in childhood, first symptoms appear at a mean age of 50 years [1,2]. The disease has a variable onset: glandular involvement with a dry syndrome and/or parotid tumefaction, or extraglandular manifestations, complicating and often delaying the diagnosis.…”
Section: Discussionmentioning
confidence: 99%